Glycosides based standardized fenugreek seed extract ameliorates bleomycin-induced liver fibrosis in rats via modulation of endogenous enzymes - Amit D Kandhare; Subhash Laxmanrao Bodhankar; Vishwaraman Mohan; Prasad A Thakurdesai (Wolters Kluwer Medknow Publications, 2017)
Background: Liver fibrosis a complex process of excess collagen deposition resulted in disturbance of hepatic cellar function. Glycosides based standardized fenugreek seed extract (SFSE-G) has potent anti-inflammatory, antioxidant, and anti-fibrotic properties. Objective: The aim of this study is to evaluate the hepatoprotective potential of SFSE-G against bleomycin (BLM)-induced liver fibrosis in laboratory animals. Materials and Methods: Sprague-Dawley rats (180-220 g) were assigned to various groups, namely, normal, sham, BLM control, SFSE-G (5, 10, 20, and 40 mg/kg, p.o.), methylprednisolone (10 mg/kg, p.o.), and sildenafil (25 mg/kg, p.o.). Liver fibrosis was induced in various groups (except normal and sham) by single intratracheal BLM (6 IU/kg) injection. Various biochemical, molecular (reverse transcription polymerase chain reaction) and histological parameters were evaluated. Results: Intratracheal BLM administration caused significant induction (P < 0.001) of hepatotoxicity and liver fibrosis reflected by elevated levels of serum aspartate transaminase (AST), alanine transaminase (ALT), total as well as direct bilirubin, and gamma-glutamyl transferase (GGT). Administration of SFSE-G (20 and 40 mg/kg, p.o.) significantly reduced (P < 0.001) levels of AST, ALT, and GGT and significantly increased (P < 0.001) the level of serum albumin. BLM-induced elevated liver oxidative stress and decreased total antioxidant capacity was significantly restored (P < 0.001) by SFSE-G (20 and 40 mg/kg) treatment. It also significantly inhibited BLM-induced alteration in liver Farnesoid X receptor (FXR) mRNA expression. SFSE-G treatment reduced histopathological alteration induced by BLM in liver. Conclusion: SFSE-G exerts its hepatoprotective potential via inhibition of oxido-nitrosative stress and modulation of FXR mRNA expression thus ameliorates BLM-induced liver fibrosis.